Perceived Stigma and Self-Efficacy among Patients with Epilepsy - Mohammed, Qahtan Q. (International Journal of Psychosocial Rehabilitation, 2020)
The study aims at assessing the levels of perceived stigma and self-efficacy among patients with epilepsy; and to determine the association between the stigma and self-efficacy. A descriptive, cross-sectional design that is initiated for the period of January 1st to June 1st, 2018. For the purpose of administrative and arrangements issues for conducting the research, the permission was asked from Al-Karkh Health Directorate and Medical City Directorate. The permission facilitates the entrance of researcher to the hospitals. The setting of the study includes the outpatient’s clinics at Baghdad Teaching Hospital and Al-Yarmook Teaching Hospital. The sample of the study includes (100) patients with epilepsy that are diagnosed by neurologists, the researcher used the convenient sampling method (non-probability sample) in which the patients were selected purposively. The questionnaire of the study is adopted by researcher which consists of three parts; the first part is contained the covering letter and the socio-demographic variable of the patients; the second part is concerned with Epilepsy Stigma Scale (ESS), and the third part is concerned with Epilepsy Self-Efficacy Scale (ESES). The data have been collected through the utilization of the self-administrative report as a mean of data collection. Statistical analyses were conducted by using statistical package for social science (IBM SPSS Statistics) version 24.0. The results indicate that people with epilepsy are showing moderate level of self-efficacy as self-management for their illness, and also they perceive a moderate level of stigma. Regarding the association between level of self-efficacy and level of stigma; the finding indicated that there no significant association between the two variables. The study concluded that self-efficacy does not influenced by stigma among people with epilepsy. The study recommended that self-management programs are required to increase the efficacy of people with epilepsy for better health outcomes and further researches are necessary for studying the various factors that may contribute to self-efficacy.